Distance learning and student motivation reinforcement during the COVID-19 pandemic through KKN Tematik UPI program - Agus Fatoni; Masharyono Masharyono (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
During the COVID-19 pandemic, the government decided to stop activities at schools. Students are forced to carry out learning activities boldly. In distance learning, several obstacles must be identified, and solutions sought. This service aims to help teachers, students, and parents deal with problems arising from implementing distance learning. One way to organize community service activities is KKN in the field of education at SDN Pancasila Lembang. The service method strengthens distance learning by selecting suitable learning media for students. Also, the implementation of talk show activities with the theme of growing student learning motivation to achieve goals. This activity is carried out to make it easy for students to carry out distance learning activities while remaining enthusiastic to reach their goals. The findings from the KKN program activities are that teachers and parents perceive positively related to the implementation of the entire program. Teachers and parents were satisfied with the series of actions that had been prepared and found it helpful to find new ways and perspectives. Also, activity programs make student learning experiences more effective and increase student motivation.   Abstrak Masa pandemi COVID-19 membuat pemerintah memutuskan untuk menghentikan kegiatan di sekolah. Para siswa terpaksa harus melaksanakan kegiatan pembelajaran secara daring. Dalam proses pembelajaran jarak jauh, terdapat beberapa kendala yang terjadi sehingga perlu diidentifikasi dan dicari jalan keluarnya. Tujuan dari pengabdian ini yaitu untuk membantu guru, siswa dan para orang tua dalam menghadapi permasalahan yang muncul dari pelaksanaan pembelajaran jarak jauh. Salah satunya cara menyelenggarakan kegiatan program pengabdian yaitu KKN pada bidang pendidikan di SDN Pancasila Lembang. Metode pengabdian yaitu penguatan pembelajaran jarak jauh dengan pemilihan media pembelajaran yang cocok untuk siswa. Juga pelaksanaan kegiatan talk show dengan tema menumbuhkan motivasi belajar siswa untuk meraih cita-cita. Kegiatan ini dilakukan untuk memberikan kemudahan bagi siswa dalam menjalani kegiatan pembelajaran jarak jauh dengan tetap semangat demi menggapai cita-cita. Temuan dari kegiatan program KKN ini yaitu bahwa para guru dan orang tua memandang positif terkait dengan penyelenggaraan keseluruhan program. Para guru dan orang tua merasa puas dengan rangkaian kegiatan yang telah disiapkan dan merasa terbantu dalam menemukan cara dan perspektif baru. Juga program-program kegiatan untuk membuat pengalaman belajar siswa menjadi lebih efektif dan juga peningkatan motivasi belajar siswa.  Kata Kunci: KKN; Kuliah Kerja Nyata; menumbuhkan motivasi; pandemi COVID-19; penguatan pembelajaran jarak jauh